Trend in the variation of sensitization of the European standard battery allergens over 26 years - Brahem, Aïcha; Gaddour, Asma; Bouhlel, Mohamed; Chouchane, Asma; Aloui, Asma; Kacem, Imen; Maoua, Maher; Kalboussi, Houda; ElMaalel, Olfa; Chatti, Souhaeil; Mrizek, Najib (International Journal of Research in Dermatology, 2021)
Background: Epidemiological monitoring of sensitization rates to common allergens and identification of emerging allergens are needed to assess preventive measures. The aim of this study was to assess trends in the frequencies of sensitization to the different allergens in the European standard battery over a 26 year period from 1989 to 2015. Methods: It’s a descriptive study of the trend of sensitization to BSE allergens over a period of 26 years, at the dermato-allergology unit of occupational medicine department of Farhat Hached university hospital-Sousse (Tunisia), based on the results of patch tests of all patients who consulted the unit between 1989 and 2015. Results: During the study period, 1716 patients were patch tested, 48048 patch tests were performed with 886 positive tests to at least one allergen (51.6%). Between 1989 and 2015, the number of positive patch tests has shown a significantly positive trend with an annual percentage change (APC) of 10.03% (p<10-3). However, the overall frequency of sensitization to BSE allergens decreased with an APC of -0.87%, p=0.2. The APC of chromium sensitization was -2.57% (p<10-3). The frequency of cobalt sensitization showed a non-significant decrease (APC=-0.28%, p=0.9). The frequency of nickel sensitization increased with an APC of +2.7%, p=0.1). Overall, there was a statistically significant growth between 1989 and 2015 in the BSE preservatives sensitization trend with an APC of +5.54% per year (p<10-3). The frequency of sensitization to mix fragrances increased from 2004 to 2015, with a significantly positive trend (APC=+24.33%, p<10-3). Conclusions: Although the frequency of some BSE allergens sensitization tends to decrease, it remains high. Consistent preventive measures should be focused, mainly on sensitization to perfumes and preservatives used in the cosmetic industry.